The highly diverged trypanosomal MICOS complex is organized in a nonessential integral membrane and an essential peripheral module. Issue 6 (3rd October 2019) - Eichenberger, Claudia; Oeljeklaus, Silke; Bruggisser, Julia; Mani, Jan; Haenni, Beat; Kaurov, Iosif; Niemann, Moritz; Zuber, Benoît; Lukeš, Julius; Hashimi, Hassan; Warscheid, Bettina; Schimanski, Bernd; et al.
Summary: The mitochondrial contact site and cristae organization system (MICOS) mediates the formation of cristae, invaginations in the mitochondrial inner membrane. The highly diverged MICOS complex of the parasitic protist Trypanosoma brucei consists of nine subunits. Except for two Mic10‐like and a Mic60‐like protein, all subunits are specific for kinetoplastids. Here, we determined on a proteome‐wide scale how ablation of individual MICOS subunits affects the levels of the other subunits. The results reveal co‐regulation of TbMic10‐1, TbMic10‐2, TbMic16 and TbMic60, suggesting that these nonessential, integral inner membrane proteins form an interdependent network. Moreover, the ablation of TbMic34 and TbMic32 reveals another network consisting of the essential, intermembrane space‐localized TbMic20, TbMic32, TbMic34 and TbMic40, all of which are peripherally associated with the inner membrane. The downregulation of TbMic20, TbMic32 and TbMic34 also interferes with mitochondrial protein import and reduces the size of the TbMic10‐containing complexes. Thus, the diverged MICOS of trypanosomes contains two subcomplexes: a nonessential membrane‐integrated one, organized around the conserved Mic10 and Mic60, that mediates cristae formation, and an essential membrane‐peripheral one consisting of four kinetoplastid‐specific subunits, that is required for import of intermembrane space proteins. Abstract : Trypanosoma brucei has a noncanonical MICOS complex required for the formation of cristae in the mitochondrial inner membrane. Here, we show that the trypanosomal MICOS is organized in two functionally specialized networks that are distinct from the ones found in yeast and mammals.